Obesity-Related Indices Are Associated with Longitudinal Changes in Lung Function: A Large Taiwanese Population Follow-Up Study - Yu-En Hsu (MDPI AG, 2021)
The global pandemic of obesity and the increasing incidence of chronic respiratory diseases are growing health concerns. The association between obesity and pulmonary function is uncertain. Therefore, this study aimed to explore associations between changes in lung function and obesity-related indices in a large longitudinal study. A total of 9059 participants with no personal histories of asthma, smoking, bronchitis, or emphysema were enrolled from the Taiwan Biobank and followed for 4 years. Lung function was assessed using spirometry measurements including forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC). Changes in FEV1/FVC (∆FEV1/FVC) between baseline and follow-up were calculated. The following obesity-related indices were studied: lipid accumulation product (LAP), body roundness index (BRI), conicity index (CI), body adiposity index (BAI), abdominal volume index (AVI), body mass index (BMI), waist–hip ratio (WHR), and waist-to-height ratio (WHtR). In multivariable analysis, the subjects with high BMI (p < 0.001), WHR (p < 0.001), WHtR (p < 0.001), LAP (p = 0.002), BRI (p < 0.001), CI (p = 0.005), BAI (p < 0.001), and AVI (p < 0.001) were significantly associated with a high baseline FEV1/FVC. After 4 years of follow-up, the subjects with high BMI (p < 0.001), WHR (p < 0.001), WHtR (p < 0.001), LAP (p = 0.001), BRI (p < 0.001), CI (p = 0.002), BAI (p < 0.001), and AVI (p < 0.001) were significantly associated with a low △FEV1/FVC. High obesity-related index values were associated with better baseline lung function and a rapid decrease in lung function at follow-up.